2019
DOI: 10.3390/cancers12010020
|View full text |Cite
|
Sign up to set email alerts
|

Management of Liver Oligometastatic Esophageal Cancer: Overview and Critical Analysis of the Different Loco-Regional Treatments

Abstract: Esophageal cancer (EC) is an aggressive disease that is associated with a poor prognosis. Since metastastic EC is usually considered suitable only for palliative therapy with an estimated 5-year overall survival (OS) less than 5%, the optimal management of patients with liver oligometastatic EC (LOEC) is still undefined. The aim of this review is to provide an overview of the different treatment options for LOEC. A literature search was conducted using PubMed, Embase, and Cochrane to identify articles evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…There is still a debate between two definitions: three to five synchronous metastatic foci in a single organ or metastatic disease affecting one or two organs with one or two foci per organ[ 11 ]. The size cutoffs accepted for oligometastatic foci is 3 cm[ 12 ]. Patients with this disease configuration could benefit from aggressive multimodal treatment with oncological treatment followed by surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There is still a debate between two definitions: three to five synchronous metastatic foci in a single organ or metastatic disease affecting one or two organs with one or two foci per organ[ 11 ]. The size cutoffs accepted for oligometastatic foci is 3 cm[ 12 ]. Patients with this disease configuration could benefit from aggressive multimodal treatment with oncological treatment followed by surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is the standard treatment for metastatic EC. With the current chemotherapy regimen, the duration of the response is short, and survival is usually 6 to 8 months [22] . Compared to the survival rate of patients who receive best supportive care, the survival rate of patients who receive chemotherapy alone is signi cantly higher (p=0.061) [16] .…”
Section: Discussionmentioning
confidence: 99%
“…The median duration of survival of 23 months and 3-year OS rate of 41 per cent respectively, in the 12 patients with head and neck SCC in the present study, compares favourably with previously reported results of 18 months and 24 per cent respectively 1 . Oesophageal cancer still represents an aggressive disease and optimal management of patients with liver oligometastatic oesophageal cancer is still undefined 24 . Adam and colleagues reported a 3-year OS rate of 32 per cent in patients who underwent liver resection for liver metastases of oesophageal cancer (both adenocarcinoma and SCC) 1 .…”
Section: Discussionmentioning
confidence: 99%